Pengaruh Kualitas Produk, Persepsi Harga, dan Varian Produk Terhadap Loyalitas Pelanggan di Mr. DIY Dhoho Plaza Kediri - Nursholikah, Yusron Wili; Murdiyanto, Edi; Mahaputra, Agung Pambudi (Wawasan : Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2025)
This study aims to examine the influence of product quality, price perception, and product variety on customer loyalty at MR.DIY Dhoho Plaza Kediri. The research method used is quantitative with a descriptive approach. The sample was determined using Slovin’s formula with a purposive sampling technique, resulting in 97 respondents from a population of 3,000. Data analysis was carried out through validity, reliability, normality, multicollinearity, heteroscedasticity, multiple linear regression, t-test, F-test, and coefficient of determination (R²) using SPSS version 25. The results indicate that product quality, price perception, and product variety have a positive and significant effect on customer loyalty, both partially and simultaneously. The coefficient of determination (R²) of 43.8% shows that these three variables are able to explain customer loyalty, while the remaining 56.2% is influenced by other factors not examined in this study.